2014
DOI: 10.1161/circulationaha.114.009480
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Long-Term Mortality After Myocardial Infarction

Abstract: Background Studies of sex differences in long-term mortality after acute myocardial infarction (AMI) have reported mixed results. A systematic review is needed to characterize what is known about sex differences in long-term outcomes and to define gaps in knowledge. Methods and Results We searched the Medline database from 1966 to December 2012 to identify all studies that provided sex-based comparisons of mortality after AMI. Only studies with at least five years of follow-up were reviewed. Of the 1,877 ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(126 citation statements)
references
References 49 publications
12
109
1
4
Order By: Relevance
“…[4][5][6][7][8]15,24,25 Compared with men, women tend to be older at the time of AMI, have more comorbidities, are less likely to receive revascularization, have longer average length of stay, and higher in-hospital mortality. 5,24,25 Results on sex differences in long-term mortality after MI have been sparse and inconsistent.…”
Section: Disparities According To Sexmentioning
confidence: 99%
“…[4][5][6][7][8]15,24,25 Compared with men, women tend to be older at the time of AMI, have more comorbidities, are less likely to receive revascularization, have longer average length of stay, and higher in-hospital mortality. 5,24,25 Results on sex differences in long-term mortality after MI have been sparse and inconsistent.…”
Section: Disparities According To Sexmentioning
confidence: 99%
“…Studies have reported less use of glycoprotein IIb/IIIa inhibitors, coronary revascularization, and statins at discharge in black versus white and female versus male MI patients. [4][5][6][9][10][11][12] Data also show that, after an initial MI event, black and female patients have greater risk of short-and long-term mortality, recurrent MI, heart failure, and stroke than white and male patients, respectively. 3 In the Medicare population, higher 30-day readmission rates for black versus white MI patients have been observed, 13 whereas, among the younger MI population (<65 years old), women have higher rates of 30-day readmission than men.…”
Section: Discussionmentioning
confidence: 97%
“…Although the incidence of hospitalized MI has decreased over the past 2 decades, rates of decline have been lower for black than for white patients, 3 and racial and sex disparities in the treatment of MI and in clinical outcomes post-MI have been described. [3][4][5][6][7][8][9][10][11][12] Significant differences in 30-day readmissions after MI between races and sexes have also been observed. 13,14 Eliminating such disparities is a national priority, 15 but achieving this goal will require a better understanding of contributing factors.…”
mentioning
confidence: 99%
“…La menor sobrevida en las mujeres en las cifras crudas puede explicarse parcialmente por la diferencia de edad, dado que eran en promedio 7 años mayores que los hombres. Varios estudios, incluida una revisión sistemática, muestran que posterior al ajuste por edad la diferencia de riesgo de muerte entre hombres y mujeres disminuye significativamente [35][36][37] . La primera evaluación realizada en Chile después del GES mostró que en las mujeres la reducción de la mortalidad intrahospitalaria fue mayor que en hombres, relacionada con el incremento en la terapia farmacológica, procedimientos de reperfusión y de revascularización en ellas 38 .…”
Section: Discussionunclassified